Contribution to the knowledge of the Anthicidae Latreille, 1819 (Coleoptera) of the Solomon Archipelago with notes on some Indo-Pacific Sapintus Casey, 1895 - Telnov, Dmitry (Zootaxa, 2024)
Anthicidae of the Solomon Archipelago, comprising the nation of the Solomon Islands and the Autonomous Region of Bougainville of Papua New Guinea, are assessed based on published records and new data. An annotated checklist and distribution maps of the Solomon Archipelago anthicids are presented. Sapintus francoisi (Pic, 1902) stat. restit., comb nov. is herein considered a valid species, removed from the synonymy with S. oceanicus (La Ferté-Sénectère, 1849), and a new combination is proposed (from Anthicus Paykull, 1798). Lectotypes are designated for Anthicus oceanicus var. guamensis Blair, 1942, A. rectifasciatus Lea, 1896, and S. oceanicus to maintain nomenclatural stability. Sapintus minamiiwo Bonadona & Sakai in Sakai, 1986 and Anthicus oceanicus var. guamensis were found conspecific with S. francoisi and new synonyms are introduced. Anthicus rectifasciatus and S. vexator (Werner, 1965) were found conspecific with S. oceanicus, and new synonyms are introduced.